Treasury of Egyptian mythology : classic stories of gods, goddesses, monsters & mortals - Napoli, Donna Jo, 1948- (National Geographic kids., 2013)
An illustrated tableau of Egyptian myths, combines narrative accounts of the stories of the Sun God Ra, the Sphinx, and numerous pharaohs and queens along with historical, cultural, and geographic facts.